ANALISA TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENYAKIT DIABETES MELLITUS DI RW 004 KELURAHAN PULOGEBANG KECAMATAN CAKUNG JAKARTA TIMUR - Nina Rustiana; Pristiyantoro; Sekar Pramudita (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Diabetes mellitus is a chronic disease characterized by high blood glucose levels and other metabolic disorders. The prevalence of diabetes is increasing significantly, and public awareness of the disease is vital for effective prevention and management. The study aims to describe the level of public awareness of diabetes mellitus in RW 004 Kelurahan Pulogebang Cakung district, East Jakarta in March 2024. The study used a quantitative descriptive method with samples of 342 respondents selected using proportional random sampling techniques. The data was collected through a validated questionnaire and tested for reliability first, which is 21 valid questions out of 25 available. Data analysis is carried out with SPSS Software Version 26.0 and is presented in the form of tables and graphs. The results of the survey showed that of the 342 respondents, 53% had good knowledge, 41% had sufficient knowledge, and 9% had less knowledge. The highest number of respondents were in the 42-45-year age range of 83 respondents (24.27%), and 102 (30%) respondents from high school with a good level of knowledge of 180 (53%) respondents. Based on the results of research carried out in RW 004 Kelurahan PuloGebang Kecamatan Cakung can conclude that the percentage of the most well-knowing was 53%, knowing quite 41%, and still there are those who know less than 9%.